Sebaran Populasi Staurastrum di Perairan Danau Sentani Jayapura - Sujarta, Puguh; Ohee, Henderite L.; Mishbach, Imam; Ngamelubun, Gerardinalia; Farmawaty, Farmawaty (Jurnal Biologi Papua, 2024)
Staurastrum is a microalgae from the family of Desmidiaceae which is abundant in freshwater. The purpose of this study was to determine the diversity of Staurastrum and the abundance of the population of Staurastrum in the Sentani Lake Jayapura. The study was conducted in March 2018 in the Sentani Lake Jayapura. The sampling method used was the survey method by sampling water in 6 locations (Kampung Yakonde, Ifale, Hobong, Kalkhote, Ayapo, Puay) on the edge and center of the lake. The results showed that 4 species of Staurastrum on the Sentani Lake were S. arachne, S. diacathum, S. gracile and S. incisum The abundance of the Staurastrum population highest at the location of Ayapo (103), Puay (94), Hobong (89), Kalkhote (81), Ifale (77) and Yakonde (8). In terms of the similarity index, there are 7 sampling points that are very similar, 23 that are similar, 20 that are dissimilar, and 16 that are very dissimilar. The difference in sampling location shows that sampling in the central part of the lakes has a higher population abundance compared to edge of the lake. In conclusion there are 4 species of Staurastrum, the location of Ayapo is higher in abundance, and the central part of the Lake is higher in abundance.    Key words: Desmidiaceae; Jayapura; Lake; Sentani; Staurastrum.